Effect of silica coating on bond strength between a gold alloy and metal bracket bonded with chemically cured resin - Ryu, Min-Ju; Gang, Sung-Nam; Lim, Sung-Hoon (Korean journal of orthodontics (2012), 2014)
The purpose of this study was to evaluate the effects of three different surface conditioning methods on the shear bond strength (SBS) of metal brackets bonded directly to gold alloy with chemically cured resin. Two hundred ten type III gold alloy specimens were randomly divided into six groups according to the combination of three different surface conditioning methods (aluminum oxide sandblasting only, application of a metal primer after aluminum oxide sandblasting, silica coating and silanation) and thermocycling (with thermocycling, without thermocycling). After performing surface conditioning of specimens in accordance with each experimental condition, metal brackets were bonded to all specimens using a chemically cured resin. The SBS was measured at the moment of bracket debonding, and the resin remnants on the specimen surface were evaluated using the adhesive remnant index. Application of metal primer after aluminum oxide sandblasting yielded a higher bond strength than that with aluminum oxide sandblasting alone (p < 0.001), and silica coating and silanation yielded a higher bond strength than that with metal primer after aluminum oxide sandblasting (p < 0.001). There was no significant change in SBS after thermocycling in all groups. With silica coating and silanation, clinically satisfactory bond strength can be attained when metal brackets are directly bonded to gold alloys using a chemically cured resin.